(untitled) (Eurasian Journal of Learning and Academic Teaching, 2021)
In this article there are considered about general didactic principles of teaching a foreign language at the higher educational establishments. The learning process is very voluminous and multifaceted. It is difficult to imagine that all principles can be relevant to the entire process. Under the principles of teaching, it is customary to consider the basic provisions that determine the nature of the learning process, which are formed on the basis of the chosen direction and the approaches corresponding to this direction. Clearly formulated training principles will help to decide how and what training content to select, what materials and techniques to use.